Investigation on temperature shrinkage characteristics of the combined structure in asphalt pavement - Jiangcai, Chen; Zhiwei, Li; Zihong, Zhao; Xiaofeng, Huang; Jie, Chen; Zhiyang, Liu (Frontiers in Materials, 2022)
The temperature shrinkage of materials primarily causes transverse cracking. Current research mainly focuses on the temperature shrinkage of single materials. This work aims to analyze the effect of the structural combination on temperature shrinkage. To this end, the temperature rise method was first discussed to measure the shrinkage coefficient to replace the traditional temperature drop method. Then, the temperature shrinkage coefficients of the lime–fly ash-stabilized macadam, and ATB and AC asphalt mixtures were measured. The effect of gradation types, lime–fly ash content, and nominal maximum aggregate size on the temperature shrinkage was studied. Finally, the temperature shrinkage of composite structural characteristics was analyzed. The results show that the difference between the temperature shrinkage coefficients obtained by temperature rise and drop methods was relatively small. Thus, the temperature rise method can be used to measure the temperature shrinkage coefficient. In addition, the lime–fly ash-stabilized macadam with the suspended dense gradation or a higher lime–fly ash content has the largest temperature shrinkage strain. The suspended dense gradation should be avoided, and the content of lime–fly ash should be approximately reduced to control the temperature shrinkage strain of the semi-rigid base course. As for the asphalt mixture, the temperature shrinkage strain increased with the decrease in the nominal maximum aggregate size. The asphalt mixture with a larger nominal maximum aggregate size should be given priority to control the temperature shrinkage. Finally, when combined with the base course or surface layer, the temperature shrinkage of the base course was promoted by the surface layer, while the base course inhibited the surface layer. Meanwhile, the mutual influence between the semi-rigid base course and the surface layer was more substantial than that of the mutual influence between the flexible base course and surface layer.